Smoking and bulimia nervosa. - Welch, S; Fairburn, C (1998)
OBJECTIVE: Little is known about the long-term physical consequences of bulimia nervosa. Some physical morbidity may result from high rates of cigarette smoking. The aim of the present study was to test three hypotheses regarding smoking among women with bulimia nervosa. METHOD: The subjects were 102 women with DSM-IV bulimia nervosa, 204 matched normal controls, and 102 matched controls with affective or anxiety disorders. All three groups were recruited from the same community sample. Interview measures were used for diagnosis and for information on smoking. RESULTS: A higher proportion of the bulimia nervosa cases were smokers than of either comparison group. Of those smokers who had achieved a period of abstinence, bulimia nervosa cases were more likely than normal control subjects to have resumed smoking, and more likely to attribute their resumption to concern about their weight. DISCUSSION: Smoking-related morbidity should be assessed in long-term follow-up studies of bulimia nervosa.